Bimbingan dan konseling di sekolah dan madrasah berbasis integrasi - Tohirin 1967- (Divisi Buku Perguruan Tinggi, RajaGrafindo Persada, 2009)
Implementation on counseling program conducted at state schools and Islamic education in Indonesia.